Application of a stability-indicating thin-layer chromatographic method to the determination of tenatoprazole in pharmaceutical dosage forms - Dhaneshwar, Sunil R.; Bhusari, Vidhya K.; Mahadik, Mahadeo V.; Santhakumari, B. (Journal of AOAC International, 2009)
A sensitive, selective, precise, and stability-indicating thin-layer chromatographic (TLC) method was developed and validated for the determination of tenatoprazole both as a bulk drug and in formulation. The method uses TLC aluminum plates precoated with Silica Gel 60(F-254) as the stationary phase and the solvent system toluene-ethyl acetate-methanol (6 + 4 + 1, v/v/v). This system gave compact spots for tenatoprazole (R(f) value of 0.34 +/- 0.02). Tenatoprazole was subjected to acid and alkali hydrolysis, oxidation, and photodegradation. The peaks of the degradation products were well-resolved from that of the pure drug and had significantly different Rf values. Densitometric analysis of tenatoprazole was performed in the absorbance mode at 306 nm. The linear regression analysis data for the calibration plots showed a good linear relationship over the concentration range of 100-1500 ng/spot. The mean values of the correlation coefficient, slope, and intercept were 0.9989 +/- 1.42, 10.27 +/- 0.965, and 4894.2 +/- 1.24, respectively. The method was validated for precision, robustness, and recovery. The limit of detection and limit of quantitation were 50 and 100 ng/spot, respectively. Statistical analysis showed that the method is repeatable and selective for estimation of tenatoprazole. Because the method can separate the drug from its degradation products, it can be used to monitor stability.